Analisis Uji Tes Toleransi Glukosa Oral Sebagai Deteksi Dini Pradiabetes Pada Obesitas - Alfyan Rahim; Thaslifa; Irwansyah (Jurnal Kesehatan Panrita Husada, 2021)
Background: Diabetes mellitus (DM) is a dangerous disease with prevalence in Indonesia, including South Sulawesi, until now it has reached 3.4% of the total population. Prediabetes is an early condition for diabetes where blood glucose levels are above normal levels. One of the factors that are most closely related to the incidence of prediabetes is obesity which is also a problem currently faced at the age of children and adolescents. One way to detect a disturbance in glucose metabolism is the Oral Glucose Tolerance Test (TTGO).Objective: This study aims to determine the incidence of prediabetes in obese students. Methods: The study design was analytical descriptive, analyzing the test variables of OGTT as a prediabetes screening in the obese. The population was all active students of Megarezky University who were obese obtained by purposive sampling technique. Results: Based on the research result of 40 respondents, after the measured levels of GDP and two-hour glucose levels after oral glucose administration (postprandial), obtained a mean grade of respondents OGTT was 120,45 mg/dl and 8 (20%) of whom had an abnormal OGTT level ( 140-199 mg/dl). Conclusion: It reveals that the eight respondents experienced impaired glucose tolerance (IGT) and prediabetes. Obese people should begin to keep a balance between intake and energy expended to avoid Diabetes Mellitus.